2014
DOI: 10.4167/jbv.2014.44.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Thein vivoandin vitroRoles of Epithelial Pattern Recognition Receptors in Pneumococcal Infections

Abstract: Streptococcus pneumoniae, also called pneumococcus, is a major cause of infectious disease in human. Pneumococcus resides in the nasopharynx as an upper respiratory commensal, and most of pneumococcal colonizations are asymptomatic in immunocompetent individuals. When nasopharyngeal mucosal homeostasis is disrupted, pneumococcus migrates into middle ear and lower respiratory tract and causes detrimental colonization. In this regard, the epithelial cells of middle ear and lung act as first line of defense again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…These findings suggested that recognition of PspK, likely the R3 domain, by annexin A2 was critical for developing or activating anti-pneumococcal immune responses and subsequent clearance of intra-epithelial pneumococci in epithelial cells. Annexin A2 activation by bacterial antigens is known to modulate Toll-like receptor (TLR) and kinase signaling pathways, which are also known to be activated by pneumococcus in epithelial cells., 35,36,49,50 Thus, further studies of PspK-annexin A2-mediated intracellular signaling pathways are required to improve our understanding of the role of this interaction in the pathogenesis of pneumococcal infections in epithelial cells. Although the mechanisms and downstream signaling pathways involved in this interaction were not fully elucidated in this study, our results provided the first evidence of a direct interaction between gram-positive bacteria and annexin A2 during the process of bacterial adherence and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that recognition of PspK, likely the R3 domain, by annexin A2 was critical for developing or activating anti-pneumococcal immune responses and subsequent clearance of intra-epithelial pneumococci in epithelial cells. Annexin A2 activation by bacterial antigens is known to modulate Toll-like receptor (TLR) and kinase signaling pathways, which are also known to be activated by pneumococcus in epithelial cells., 35,36,49,50 Thus, further studies of PspK-annexin A2-mediated intracellular signaling pathways are required to improve our understanding of the role of this interaction in the pathogenesis of pneumococcal infections in epithelial cells. Although the mechanisms and downstream signaling pathways involved in this interaction were not fully elucidated in this study, our results provided the first evidence of a direct interaction between gram-positive bacteria and annexin A2 during the process of bacterial adherence and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of tympanosclerosis is not clearly understood yet, the prolonged inflammation or delayed resolution of middle ear inflammation is thought to significantly contribute to the pathophysiology of tympanosclerosis. We previously reported that Streptococcus pneumoniae, another common bacterial pathogen in OM, up-regulates PAI-1, and PAI-1 plays a critical role in protecting against S. pneumoniae-induced acute lung injury in severe pneumococcal pneumonia [19,20]. These findings suggest a possible role of PAI-1 in regulating S. pneumoniae-induced OM.…”
Section: Discussionmentioning
confidence: 76%
“…These data suggest that pneumococcus may regulate TLR2 expression and subsequent innate immune responses through the regulation of TBX21 expression. As TLR4 and TLR9, along with TLR2, act as critical receptors for pneumococcus (Shin et al ., ), the effects of D39 and siTBX21 on TLR4 and TLR9 expression were also determined. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%